Group lending through an SHG bank-linkage programme in India: transaction costs and social benefits. Issue 2 (17th February 2020) - Rajeev, Meenakshi; Vani, B. P.; Veerashekharappa
ABSTRACT: Group lending is useful in channelling credit to the self-employed poor in developing countries, to whom banks usually prefer not to lend, and formation of self-help groups (SHGs) helps facilitate this. In India, SHGs can access credit through private microfinance organisations or can approach banks through a state-led bank-linkage programme. Scholars argue that transaction costs are high while borrowing from banks despite relatively lower interest rates, making this uneconomical. This article uses a field survey to estimate transaction costs, presents other social benefits of the programme, and finds empirical justifications for strengthening the bank-linkage programme.